RSK3 is required for concentric myocyte hypertrophy in an activated Raf1 model for Noonan syndrome - Passariello, Catherine L. (J Mol Cell Cardiol, 2016)
Noonan syndrome (NS) is a congenital disorder resulting from mutations of the Ras-Raf signaling pathway. Hypertrophic cardiomyopathy associated with RAF1 “RASopathy” mutations is a major risk factor for heart failure and death in NS and has been attributed to activation of MEK1/2-ERK1/2 mitogen-activated protein kinases. We recently discovered that type 3 p90 ribosomal S6 kinase (RSK3) is an ERK effector that is required, like ERK1/2, for concentric myocyte hypertrophy in response to pathological stress such as pressure overload. In order to test whether RSK3 also contributes to NS-associated hypertrophic cardiomyopathy, RSK3 knock-out mice were crossed with mice bearing the Raf1(L613V) human NS mutation. We confirmed that Raf1(L613V) knock-in confers a NS-like phenotype, including cardiac hypertrophy. Active RSK3 was increased in Raf1(L613V) mice. Constitutive RSK3 gene deletion prevented the Raf1(L613V)-dependent concentric growth in width of the cardiac myocyte and attenuated cardiac hypertrophy in female mice. These results are consistent with RSK3 being an important mediator of ERK1/2-dependent growth in RASopathy. In conjunction with previously published data showing that RSK3 is important for pathological remodeling of the heart, these data suggest that targeting of this downstream MAP-kinase pathway effector should be considered in the treatment of RASopathy-associated hypertrophic cardiomyopathy.